Rumen parameters and passage rate in cattle fed diets based on sugarcane hydrolyzed with calcium oxide - Fernando César Ferraz Lopes (Semina: Ciências Agrárias, 2018)
Nine non-lactating Holstein x Gyr cattle were fed with rations based on chopped sugarcane supplied in natura (control) or hydrolyzed (fresh matter basis) for 24 h with 1% or 2% calcium oxide (CaO), which corresponds to 3.1% or 6.2% CaO on a dry matter (DM) basis, respectively. Ruminal parameters (pH and ammonia N, acetate, propionate and butyrate concentrations) as well as the kinetics of fluid and particulate passage in the gastrointestinal tract from cattle were evaluated. A design using three 3 x 3 contemporaneous Latin Squares (LS) was adopted. The studies of kinetics of fluid and particulate passage were performed using the external markers cobalt-EDTA and chromium-mordanted-NDF, respectively. The ruminal parameters were analyzed according to a 3 x 3 LS replicated three times with repeated measures in time using mixed models that included the fixed effects of treatment (level of CaO), time of sampling and their interaction and the following random effects: LS, animal(LS), period of LS and period*animal (LS). The kinetic parameters of fluid and particulate passage were analyzed using mixed models with treatment as a fixed effect and period of LS, animal(LS) and LS as random effects. The linear and quadratic effects of the treatments were analyzed using orthogonal contrasts. Significant differences were declared at P ≤ 0.05. No treatment*time interaction was observed (P > 0.05) for any ruminal parameter. A linear effect (P = 0.0279) of CaO inclusion on ruminal pH was observed, but there were no effects (P > 0.05) of the treatments on the ammonia N, acetate, butyrate and total volatile fatty acid ruminal concentrations. There was a quadratic effect (P = 0.05) of the addition of CaO on the ruminal propionate concentration. There was no effect (P > 0.05) of the treatments on the particulate rate of passage in the rumen as well as on the mean retention time in this compartment and in the total gastrointestinal tract. On the other hand, the addition of CaO to sugarcane promoted a linear increase (P = 0.0258) in the particulate post-ruminal passage rate and, consequently, a linear reduction (P = 0.0363) of the mean retention time in the cecum-proximal colon. There was no effect (P > 0.05) of the sugarcane hydrolysis with CaO on the ruminal parameters of the kinetics of fluid passage (dilution rate, retention time and turnover rate). The addition of 3.1% or 6.2% CaO on a DM basis (1% or 2% CaO on a fresh matter basis, respectively) of sugarcane does not improve ruminal fermentation, nor does it increase the fluid or particulate passage in the rumen of non-lactating Holstein x Gyr cattle.